Improved modified a multi-level inverter with a minimum total harmonic distortion - Khalid M. Abdulhassan; Osama Yaseen Khudair Al-Atbee (Institute of Advanced Engineering and Science, 2022)
Renewable energy sources are developed as a result of the increased demand for electrical power. The nature of the solar energy source is DC. The DC source for many applications needs to be converted to AC. The inverter is used to convert the power from DC to AC. Total harmonic distortion (THD) is a significant concern with inverters. Multi-level inverters are used to reduce the THD. The stair output voltage of the multi-level inverter not only reduces the THD but also reduces the switches' stresses, so a low voltage rating can be used for the switches. In this paper, a modified inverter topology is introduced in which the number of switches is reduced for the same number of output voltage levels, which leads to reducing the losses and the cost. To reduce the THD, different amplitudes for the carrier signals that control the switches in each level are suggested. Another method to reduce the THD by using different capacitor values across the input DC source is presented. The MATLAB/Simulink is used to show the validity of the suggested modified topology and the modifications.